Traditional uses of medicinal plants reported by the indigenous communities and local herbal practitioners of Bajaur Agency, Federally Administrated Tribal Areas, Pakistan. (23rd February 2017) - Aziz, Muhammad Abdul; Khan, Amir Hasan; Adnan, Muhammad; Izatullah, Izatullah
Abstract: Ethnopharmacological relevance: In the study area, knowledge related to the traditional uses of medicinal plants is totally in the custody of elder community members and local herbalists. The younger generation is unaware of the traditional knowledge, however with only few exceptions. Therefore, this study was planned with objective to document the medicinal importance of plants, conserve this precious indigenous knowledge, and share it among other communities through published literature. Materials and methods: Data was collected through semi-structured interviews from the community members and local herbalists. The reported plants were collected post interviews and later on pressed on herbarium vouchers for reference. Afterwards, the data was analyzed through Use value (UV) and Relative Frequency of Citation (RFC). Results: In total, 79 medicinal plant species were used for the treatment of different ailments in the study region. Out of the total plant species, 28 species were not reported from any other mountainous communities across the country. In this study, the ethno-medicinal value of Opuntia littoralis (Engelm.) Cockerell and Viola indica W.Becker was reported for the first time, which have moderate confidential level in terms of their medicinal uses in the study area. Important medicinal plants of the region with high UV are Berberis lycium Royle (0.94), V. indica (0.90), Isodon rugosus (Wall. ex Benth.) Codd (0.88), Foeniculum vulgare Mill. (0.87), Peganum harmala L (0.86), Solanum virginianum L. (0.85), and Cassia fistula L. (0.79). Medicinal plants with higher RFC values are Calotropis procera (Aiton) Dryand. (0.86), Cannabis sativa L. (0.82), Mentha piperita L. (0.82), Mentha longifolia (L.) Huds. (0.76), Allium sativum L. (0.73), Coriandrum sativum L. (0.73), and F. vulgare (0.72). Conclusions: Traditional knowledge on folk medicines is directly linked to the local culture, faith and perception. This knowledge is gaining high threat of extinction because of its limitation to a small portion of the society in the region. Therefore, future studies are recommended in similar regions for the documentation of this precious knowledge. Moreover, our study has also identified some important and newly reported medicinal plants from the ethno-medicinal perspective, which needs to be studied pharmacologically and toxicologically. Graphical abstract: Ethnomedicinal survey of important plants practiced by indigenous community at Ladha subdivision, south Waziristan agency, Pakistan.